BREAST CANCER IN PREGNANCY AT DR. KARIADI GENERAL HOSPITAL: A SERIAL CASE - Ireneus Vanessa Martono; M. Besari Adi Pramono; Herman Kristanto; Albertus Ari Adrianto (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background Each year 2.1 million women were diagnosed with breast cancer, being the most common type of cancer found and cancer-related cause of death in women worldwide. In Indonesia, especially in Middle Java, more than 80% women diagnosed were already in the late stage. Physiological changes in pregnancy contributes to the delay in diagnosis in pregnant women and pregnancy also resulted in a more complicated approach of therapy. Regarding only few studies were done involving pregnancy with breast cancer, the aim of the study is to provide further knowledge associated with it.Methods Medical records of pregnant women with breast cancer in year 2014-2018 at Dr. Kariadi General Hospital were studied.Results Based on the 3 cases be studied, patients were referred from class B and C hospitals outside of Semarang city showing stage III (33.33%) and IV (66.67%) breast cancers. Two-third of the patients underwent mastectomy previously and one of them also underwent chemotherapy program prior her pregnancy. Comorbidities varied between patients and therapies were adjusted individually and multidisciplinary. Two of the cases went through transperitoneal caesarean section for delivery and one patient with twin pregnancy died by complications and intrauterine foetal death was also determined.Conclusion Overall, all patients were > 35 years old and the breast cancers were diagnosed at late stage. Complications by comorbidities such as anaemia, severe malnutrition, and infection, were found. Two pregnancies which were already in third trimester was terminated and a case of maternal mortality was found.Keywords Breast cancer, pregnancy